New variants of poly(beta amino esters) to enhance delivery of nucleic acid medicines - Bayraktutan, Hulya (2024)
Nucleic acid technology is now acknowledged as a versatile and potent medical platform enabling transient protein expression for vaccines against infectious diseases and therapeutics targeting genetic disorders and cancer. The successful safety and efficacy demonstration of Moderna's SpikeVax and BioNTech-Pfizer's Comirnaty mRNA-based COVID-19 vaccines has greatly accelerated the field, with numerous nucleic acid vaccines and therapeutics now in clinical trials. While mRNA vaccines gained popularity during the COVID-19 crisis, the inherent stability of DNA in comparison to mRNA suggests that DNA technologies might find broader use, especially in low to middle income countries facing limitations in cold-chain storage accessibility. A crucial aspect of effective nucleic acid medicine is a safe and efficient delivery system to safeguard the genetic sequence from endogenous nucleases and facilitate translocation into target cell cytosol for expression. Various nonviral delivery strategies, including lipid nanoparticles (e.g., liposomes, cubosomes) and polyelectrolyte complexes (polyplexes), have been explored for nucleic acid delivery. Polyplexes, self-assemblies of positively charged polymers condensing negatively charged nucleic acids into small nanoparticles (50-200 nm), are promising for nucleic acid delivery. Poly(beta-amino esters) (PBAEs), a class of polycations, are extensively investigated as nucleic acid delivery vectors due to their biodegradability via hydrolysis, allowing enhanced nucleic acid release. However, the polycationic content and the hydrophobic side-chains of some PBAEs' can induce cytotoxicity through membrane disruption, as well as compromise their colloidal stability and alter their potential immunogenicity profile limiting their clinical utility. Therefore, in this thesis, we aimed to investigate new PBAE-based polymers through end-modification approaches, such as the conjugation of hydrophilic polymers or a ligand, to enhance their physicochemical properties. These modifications are intended to increase stability or enable targeted delivery, making them more effective as potential gene carriers. Previous studies have demonstrated that coupling PBAEs with poly(ethylene glycol) (PEG) reduces surface cationic charges when complexed with nucleic acids, potentially mitigating toxicity and decreasing interactions with serum proteins. This approach has been shown to prolong systemic nanoparticle circulation time by shielding their surface from aggregation and phagocytosis, consequently increasing in-serum in vitro and in vivo transfection efficacy. Therefore, we focused on optimizing PBAE properties, particularly surface PEG density, for effective pDNA encapsulation and gene transfection in vitro. Then, selected formulations were further evaluated in vivo to investigate their potential as a SARS-CoV-2 pDNA vaccine and revealed that one formulation led to strong antigen specific T-cell responses. In addition, PBAEs were further investigated via end-capping with polysarcosine (pSar) as an alternative to PEGylation, and as potential RNA carriers. Then, the efficacy of newly synthesised formulations was explored using human-derived colon colorectal organoids. The selected formulations displayed high transfection ability within the core of organoids indicating high penetration of these nanoparticles. As a result, these findings indicate that pSarylated PBAEs have the potential to serve as a promising component material for enhancing delivery of nucleic acid therapeutics. Further optimization of PBAEs as enhanced gene delivery vehicles was achieved by conjugating a Toll-like receptor 7 (TLR7) agonist (loxoribine) to enhance the robustness of immune response. Synthesised polymers were formulated using RNA and investigated in vitro using different types of cell lines. TLR activation assays showed that loxoribine-conjugated formulations can efficiently agonise TLR7 with some synergy observed between loxoribine and the delivered RNA. Consequently, these findings suggest the potential of adjuvanted polyplexes for enhanced mRNA vaccines. Overall, the studies in this thesis revealed that the choice of end-capping agent significantly impacts PBAE-based polymer properties and effectiveness in nucleic acid delivery. The findings emphasized the importance of surface properties in polymer delivery systems, showing potential for vaccination and tumor delivery.